Stability of Morphophysiological Characters, Tuber Yield, and FBPase Gene Expression in Transgenic Potato Cultivar IPB-CP3 - Suaidi, Malik Nuris; Tjahjoleksono, Aris; Miftahudin, M (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Potatoes are an essential agricultural commodity that needs to be genetically improved to increase productivity and meet industrial needs. The research aimed to evaluate the stability of the morpho-physiological characters, tuber yield, and transgene expression of transgenic potato cultivar IPB-CP3 harboring the FBPase gene in the G0 and G1 generations. The study was conducted by growing transgenic plants in a greenhouse and analyzing plant morpho-physiological characters, tuber yield, and gene expression. The results showed that transgenic plants had higher values in stem diameter (32.7–50.8%), number of leaves (33.9–41.2%), biomass dry weight (14.4–36.2%), photosynthetic rate (25.2–28.25%), and tuber weight (42.6–196.0%) than non-transgenic plants. However, there was no significant difference in plant height characters between the transgenic and non-transgenic plants. Transgenic plants consistently expressed the FBPase gene at higher level than the non-transgenic plants in the G0 and G1 generations. The research results suggest that overexpression of the FBPase gene increases plant growth and tuber yield. This finding implies agricultural practices, particularly in the context of crop improvement through genetic engineering.